Quality and competitiveness diagnostic of tourism industry in Mexico - Ibáñez Pérez, Reyna María (Cuadernos de Turismo, 2011)
The globalization of world economy intensifies the competition between tourist destinations. Given this, it is necessary to make efforts to maintain the privileged position currently enjoyed by some countries. Such is the case of Mexico, which is distinguished as one of the leaders in the global tourism market by occupying the tenth position in the reception of visitors, although this has not yet established a culture of quality and competitiveness, as a result shows a tendency to linger in the competitiveness ranking of the top tourist destinations in the world.